The Effect of Market Attractiveness and Company Capability on Emergent Value Creation Strategy and Sustainable Company Performance (A Study of Digital Industry Service Companies in Jakarta) - Chairudin Mirza Taufik; Mohamad Rizan; Muhammad Awaluddin (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This study examines how market conditions and organizational capability are translated into sustainability-oriented performance, with Emergent Value Creation Strategy (EVCS) considered as a mediating process. The data were obtained from 50 owners and managers of digital creative service firms operating within a telecommunications incubation ecosystem in Jakarta. A quantitative explanatory approach was applied, and the higher-order measurement and mediation model was estimated using partial least squares structural equation modeling. The results show that both Market Attractiveness and Company Capability are positively associated with EVCS. Company Capability also has a significant direct relationship with Sustainability Company Performance, while EVCS records the largest direct coefficient for that outcome. Market Attractiveness, however, does not significantly affect performance through a direct path. Its effect is transmitted through EVCS, whereas the effect of Company Capability is only partly mediated. These findings indicate that an attractive market creates possibilities rather than assured results. Economic, social, and environmental performance becomes more likely when market insight is supported by usable resources and stakeholder-oriented routines involving dialogue, access, risk assessment, and transparency. The study contributes to research on digital service firms by explaining emergent value creation as the process through which external opportunity and internal capability are connected with multidimensional sustainability performance.